Evaluating Groundwater Quality and Behavior at UWEC Campus - Gorg, Madelynn; Hook, Glen; Vitale, Sarah A. (My University, 2019)
To garner a better understanding of groundwater flow and water quality on the University of Wisconsin –Eau Claire campus, we collected monthly measurements in fourteen (14) monitoring wells across lower campus, including seven (7) wells installed over the summer of 2018. The parameters measured included temperature, pH, dissolved oxygen, oxidation-reduction potential, specific conductance, and nitrate, measured. Pressure transducers were also installed in two wells near the Chippewa River to continuously monitor hourly changes in water level. This project was a directed study integrated with a field-based laboratory component in the Contaminant Hydrogeology course in the Geology Department.
Color poster with text, images, charts, photographs, and graphs.
Keywords: Groundwater; University of Wisconsin--Eau Claire; Posters; Department of Geology